2007
DOI: 10.3354/cr033207
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between genetic diversity and temperature stress on life-cycle parameters and genetic variability in midge Chironomus riparius populations

Abstract: The genetic diversity of natural populations and the increase in global temperature are becoming important issues in ecotoxicological research. We investigated the combined effects of 3 different temperature levels and 6 different levels of genetic diversity on the life history parameters of Chironomus riparius. Inbreeding and loss of genetic variation are major threats to small and endangered populations. The reduction of fitness due to inbreeding is more severe under stressful environmental conditions. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
(10 reference statements)
2
18
0
Order By: Relevance
“…Nowak et al (2007a) for instance showed that inbreeding and reduced genetic variation lead to increased sensitivity towards Cd-exposure in a laboratory experiment using three midge strains with different levels of genetic variability. This result was confirmed in two similar studies with temperature stress (Vogt et al 2007c;Oetken et al 2009). Furthermore, Nowak et al (2007b) showed that the level of genetic diversity significantly impacts the outcome of chemical exposure studies with different laboratory strains of C. riparius.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nowak et al (2007a) for instance showed that inbreeding and reduced genetic variation lead to increased sensitivity towards Cd-exposure in a laboratory experiment using three midge strains with different levels of genetic variability. This result was confirmed in two similar studies with temperature stress (Vogt et al 2007c;Oetken et al 2009). Furthermore, Nowak et al (2007b) showed that the level of genetic diversity significantly impacts the outcome of chemical exposure studies with different laboratory strains of C. riparius.…”
Section: Discussionsupporting
confidence: 88%
“…The natural logarithm of time (in days) was taken and the number of emerged midges was cumulated and normalised to percentages for each replicate. Afterwards, a non-linear regression was performed (logistic curve, maximal response 100%) of which the EmT 50 is a parameter (for details see Vogt et al 2007c). This parameter could only be determined for treatments with a mortality below 80%, because in these cases meaningful values were generated.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…T tests were used in order to reveal significant differences among species within treatments. EmT 50 was calculated according to Vogt et al (2007c).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Additional EmT 50 values at 17, 20, 23, 24 and 288C were taken from the literature [35][36][37]. These data were fitted to an exponential decay function (electronic supplementary material, S1.1).…”
Section: (C) Estimation Of Temperature-dependent Generation Timementioning
confidence: 99%